The Impact of Online Platforms on Generation Z's Learning Styles and Educational Outcomes: A Comprehensive Study - Elfindah Princes (Journal of Multidisciplinary Issues, 2024)
Purposes - This study aims to investigate the relationship between material comprehension and satisfaction among Generation Z learners using online platforms. Specifically, it examines how variations in material comprehension influence overall satisfaction with the learning experience. The research also explores possible indirect effects of other variables, such as motivation, on this relationship. Methodology - The study employed a quantitative research design, collecting data from 51 respondents. A path coefficient analysis was conducted to evaluate the direct and indirect effects of material comprehension on satisfaction. The data were analyzed using bootstrapping methods to determine the significance of the relationships between the variables. Findings - The analysis revealed that material comprehension significantly impacts satisfaction (p-value = 0.002), with higher levels of comprehension leading to greater satisfaction. Additionally, learning motivation was found to have both direct and indirect effects on satisfaction through its influence on material comprehension. However, some anomalies were observed where high comprehension did not always correlate with high satisfaction, indicating the influence of other factors. Novelty - This research contributes to the growing body of literature on Generation Z learning by focusing on the relationship between comprehension and satisfaction in online learning environments. The study also highlights the importance of understanding the role of motivation in enhancing both comprehension and satisfaction, offering new insights into the dynamics of digital education. Research Implications - The findings have important implications for educators and policymakers, suggesting that efforts to improve material comprehension can significantly enhance student satisfaction in online learning environments. Moreover, the study highlights the need to address motivational factors to maximize learning outcomes. Future research should explore additional variables that may mediate or moderate the relationship between comprehension and satisfaction.